Asuhan Keperawatan Keluarga Tn. A dengan Gangguan Sistem Persyarafan: Stroke di Desa Kalibuntu RT 04 RW 03 Kecamatan Losari Kabupaten Brebes - Farid Munada; Siti Fatimah; Slamet Wijaya (STIKES Columbia Asia Medan, 2024)
Stroke is a type of cerebrovascular disease in which blockage, narrowing or rupture of blood arteries supplying the brain results in brain infarction or loss of brain tissue. This writing aims to analyze the process of family nursing care given to Mr. A, a stroke patient in Kalibuntu Village, Brebes Regency. A, a stroke patient in Kalibuntu Village, Brebes Regency, starting from assessment, nursing diagnosis, planning, implementation to evaluation. This writing uses a qualitative descriptive approach with a case study as the writing design. Data collection was done through in-depth interviews with the patient and family, as well as direct observation of the interaction between the nurse and the patient's family. The results of the writing are expected to contribute to the improvement of an effective family nursing care model for stroke patients in the community.